The Prevalence of Increasing Uric Acid and Blood Pressure in Elderly People at Panti Jompo Werdha Tresna in Gianyar Bali (Preliminary Studies) - Dakshayani Vijayan; Linawati Ni Made (Faculty of Medicine, Udayana University, 2017)
The prevalence of increasing of uric acid and blood pressure is high in elderly people. Most of old people who suffer from high uric acid also do suffer from high blood pressure. This will eventually lead to many diseases which may lead to chronic condition or even death. The purpose of this study was to know the prevalence of increasing uric acid and blood pressure in elderly people at Panti Jompo Werdha Tresna in Gianyar Bali. The method of research is cross sectional descriptive observational. The research sample is 20 people which consist of 5 male and 15 female from the Panti Jompo Werdha Tresna in Gianyar Bali who is aged from 60-80 years old. The individual was chosen randomly with their permission.Based on the research we found that the level of uric acid which was high is for 9 person (45%) and 11 person (55%) of them have normal range of uric acid level. The person who suffering from normotension is 9 person (45%), prehypertension is 6 person (30%) and lastly hypertension is only 5 person (25%). The number of population who suffer from hypertension and they also have elevated value of uric acid is 4 person (44.4%). It can be concluded that age was not a risk factor for the increasing level of uric acid and blood pressure because the sample that was very small .Old people should be given proper guidance to a healthy lifestyle.Keywords: uric acid, blood pressure, old people